Properties of asiaticoside in suppressing hyperpermeability in human umbilical vein endothelial cells induced by interferon-gamma - Khairudin, Nurnabila Huda (2016)
Impairment of endothelial barrier function by vasoactive agents or inflammatory mediators promotes endothelial hyperpermeability causing the development of pathological conditions such as tissue oedema. The changes of barrier structure caused gaps formation thus promote vascular leakage of plasma fluid and macromolecules. Interferon-gamma is a well-known pro-inflammatory mediator which disturbed barrier integrity thus promotes hyperpermeability on endothelial cell. Several studies have reported that asiaticoside; a triterpenoid derived from Centella asiatica (local - pegaga) exhibits good anti-oxidant properties, wound healing, immunomodulatory, as well as anti-inflammatory effects on several inflammatory models. In order to elucidate the potential properties of asiaticoside on endothelial barrier preservation, its actions on Human Umbilical Vein Endothelial Cell (HUVEC) hyperpermeability induced by interferon-gamma was assessed. It has been found that interferon-gamma caused an increased in endothelial permeability, determined by the flux of fluorescein isothiocyanate-dextran through in vitro permeability assay. Pre-treatment of asiaticoside to interferon-gamma-activated HUVEC significantly (p < 0.05) attenuated endothelial hyperpermeability. Moreover, it was clearly demonstrated that asiaticoside helps in restoration of nitric oxide; a mediator which regulates barrier integrity and permeability regulator, back to its basal state after impairment by interferon-gamma. p38 Mitogen Activated Protein Kinase signalling pathway is believed to be involved in nitric oxide production. Thus, it was clearly clarified that p38 Mitogen Activated Protein Kinase phosphorylation, conducted via western blot analysis was deactivated after treatment with asiaticoside. For further clarification, cyclooxygenase-2 level as well as prostaglandin E2 release in interferon-gamma-activated HUVEC was also studied. Interferon-gamma has increased cyclooxygenase-2 level and prostaglandin E2 release but also stabilized by asiaticoside. These results suggest that asiaticoside regulated endothelial barrier preservation via p38 Mitogen Activated Protein Kinase phosphorylation and nitric oxide restoration. Our results suggest that asiaticoside may become an important remedy in endothelial barrier preservation induced by interferon-gamma.